ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE PADA PT BANK SYARIAH INDONESIA (BSI) TBK. KOTA MEDAN DALAM PERSPEKTIF REGULASI DAN KINERJA PERUSAHAAN - Adisty Aulia Zahra; Ahmad Wahyudi Zein; Elvira Andriyani; Popi Dea Ananda; Salsabila Sofiya Wardani (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) at PT Bank Syariah Indonesia (BSI) Tbk. Medan City from the perspective of regulation and corporate performance. Good Corporate Governance is a crucial principle in ensuring transparency, accountability, responsibility, independence, and fairness in the management of Islamic banking institutions. This research employs a descriptive qualitative approach, with data collected through document analysis, company annual reports, relevant Islamic banking regulations, and supporting literature. The results indicate that PT Bank Syariah Indonesia Tbk. Medan City has implemented Good Corporate Governance principles in accordance with regulatory provisions, particularly those issued by the Financial Services Authority (Otoritas Jasa Keuangan/OJK) and Bank Indonesia. The implementation of GCG is reflected in the organizational structure, internal control systems, regulatory compliance, and continuous management supervision. Furthermore, the application of Good Corporate Governance contributes positively to the improvement of corporate performance, both financially and non-financially, such as increased customer trust and operational stability. Nevertheless, further strengthening of evaluation and supervisory mechanisms is required to ensure that the implementation of Good Corporate Governance can be carried out more optimally and sustainably in the future.